Risk Factors for Contamination of Pesticide Residues in Women's Breast Milk Farmers in Agricultural Ar-eas - Rachmawati, Intan; Hernawati, Sri; Sulistyaningsih, Erma; Muhammad, Aldi Cahya (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Pesticides are all chemicals, serve as controls for pests and weeds' growth. This study aimed to identify the pesticide residue contamination in women farmers' breast milk in agricultural areas and analyze the risk factors. Quantitative descriptive research method with cross-sectional approach. A sample of 10 female farmers was selected using the purposive sampling technique. Data on risk factors were obtained by interview using a questionnaire, and pesticide residues in breast milk were measured by GC-MS/MS and LC-MS/MS. Spearman rank correlation tests and ordinal logistic regression are used to analyze data. The results showed that all of the respondents' breast milk was contaminated with organochlorine pesticide p'p DDE (> 0.001 mg/kg). Statistical test results prove that nutritional status / BMI with pesticide residue concentration has a significant relationship (p-value = 0.000). In conclusion, excess body mass index is a risk factor for pesticide residue contamination in female farmers in agricultural areas.